ANALISIS PELAKSANAAN KONSELING KELOMPOK DALAM MENGURANGI KECEMASAN AKADEMIK MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING DI IAKN TORAJA - Lusiana; Delpa Sombo Madulu'; Jelsia Panggalo; Yuyun Paliran; Wanny Farma Kasi (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
This study aims to analyze the implementation of group counseling in reducing academic anxiety among students of the Guidance and Counseling Study Program at the State Christian Institute (IAKN) Toraja. The research employs a qualitative approach with a descriptive method to gain an in-depth understanding of the service implementation process, influencing factors, service effectiveness, and implications for the development of guidance and counseling services in higher education. Data were collected through observation, interviews, and documentation, and subsequently analyzed using the interactive analysis model developed by Miles, Huberman, and Saldaña. The results indicate that systematically conducted group counseling helps students reduce academic anxiety by fostering self-disclosure, emotional management skills, self-confidence, and problem-solving abilities. The success of the service is influenced by counselor competence, active student participation, group dynamics, and institutional support. Beyond reducing academic anxiety, group counseling contributes to the development of guidance and counseling services that are more preventive, comprehensive, and oriented toward student psychological well-being within the higher education environment.